2020
DOI: 10.1186/s12891-020-03810-4
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for cement leakage and nomogram for predicting the intradiscal cement leakage after the vertebra augmented surgery

Abstract: Background Vertebral augmentation is the first-line treatment for the osteoporosis vertebral compression fractures. Bone cement leakage is the most common complication of this surgery. This study aims to assess the risk factors for different types of cement leakage and provides a nomogram for predicting the cement intradiscal leakage. Methods We retrospectively reviewed 268 patients who underwent vertebral augmentation procedure between January 2015 and March 2019. The cement leakage risk factors were evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
34
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(37 citation statements)
references
References 27 publications
3
34
0
Order By: Relevance
“…IVC formation in the osteoporosis vertebral compression fracture was signi cantly associated with the poor prognosis of the patients [1][2][3]. Therefore, the pathogenesis of the IVC received much attention.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…IVC formation in the osteoporosis vertebral compression fracture was signi cantly associated with the poor prognosis of the patients [1][2][3]. Therefore, the pathogenesis of the IVC received much attention.…”
Section: Discussionmentioning
confidence: 99%
“…However, the OVCF with intravertebral cleft (IVC) formation was always indicating a poor prognosis even after the vertebral augmentation surgery. Complications such as cement leakage [1], augmented vertebra recollapse (Fig. 1 f, g) [2], and the adjacent vertebral fracture [3] were more common in IVC patients.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Recent studies reported the prevalence of intra-spinal canal cement leakage ranged from 2.70% to 13.58% among patients with osteoporotic vertebral fractures treated with PVP. 12 , 13 Intra-spinal canal cement leakage may lead to severe complications and even disability. Therefore, a risk model that can evaluate the risk of intra-spinal canal cement leakage was clinically essential.…”
Section: Discussionmentioning
confidence: 99%
“…New predictive models, including lasso regression and nomogram based on multiple logistic regression, have been developed and validated to predict postoperative vertebral compression fractures [12,13] . As far as we know, this is the first attempt to develop a nomogram-based method for adjacent vertebral fractures after vertebroplasty.…”
Section: Introductionmentioning
confidence: 99%